Ves-Matic CUBE 200: is modified Westergren method for erythrocyte sedimentation rate a valid alternative to the gold standard?. Issue 10 (1st June 2019) - Lapić, Ivana; Piva, Elisa; Spolaore, Federica; Musso, Giulia; Tosato, Francesca; Pelloso, Michela; Plebani, Mario
Abstract : Ves-Matic CUBE 200 is an automated erythrocyte sedimentation rate (ESR) analyser based on the modified Westergren principle of measurement. In this study, we aimed to assess its analytical performance following the key points addressed by the International Council for Standardization in Haematology and the comparability with the gold standard Westergren method. Comparison of the two methods yielded a correlation coefficient of 0.852, no significant bias and a small constant difference between compared results. Intrarun coefficients of variation (CV) ranged from 2.2% to 22.2%, the higher being for lower ESR values, while inter-run CVs were 19.7% for the normal range and 3.0% for the abnormal range. This study proved the analytical validity of the Ves-Matic CUBE 200 and its high comparability with the Westergren method, showing obvious improvements in the technology applied for automated determination of ESR and a valuable step forward in standardisation of ESR methods.